Impact of smoking and physical inactivity on self-rated health in women in Colombia (2019)
The aim of this study was to assess the association between poor and fair self-rested health, smoking, and leisure-time physical inactivity in Colombian women. A cross-sectional study using the data from the 2010 Colombian National Demographics and Health (ENDS) and Nutritional Situation (ENSIN) Surveys was conducted. Multivariate logistic analysis for self-perceived health status in 12,431 women aged 13–49 years old and 8224 women aged 18–64 years old were performed. Independent variables included smoking, leisure-time physical inactivity, anthropometric and socio-demographic information. Current smoking and leisure-time physical inactivity were associated with poor and fair self-rated health status (OR 1.78, CI 1.41, 2.25; OR 1.30, CI 1.03, 1.62; respectively). Other significantly associated variables were age (OR 1.68, CI 1.46, 1.92 for 30–49 years; OR 2.32, CI 1.96, 2.74 for 50–64 years), socio-economic strata (OR 7.24, CI 3.81, 13.76 for strata 1–3), educational level (OR 1.70 to 2.77 compared to technical or university), obesity (OR 0.81, CI 0.70, 0.93 for normal body mass index), geographical region (OR 0.67, CI 0.53, 0.85 for Bogotá, compared to Amazon and Orinoco regions), and no affiliation to health system (OR 1.22, CI 1.03, 1.44). Smoking and leisure-time physical inactivity were significantly associated with poor and fair self-rated health in Colombian women. Promoting leisure-time physical activity and implementing smoking cessation strategies specifically in female population, mainly from low to medium strata are suggested to improve their self-perceived health status and control chronic noncommunicable diseases. © 2019